Integrated Translational and Rotational Control for the Final Approach Phase of Rendezvous and Docking. Issue 5 (8th March 2018) - Yan, Han; Tan, Shuping; Xie, Yongchun
Abstract: This paper presents an approach of integrated translational and rotational control (ITRC) design for the final approach phase of rendezvous and docking on an ellipse orbit. First, considering the uncertainties, the integrated translation and rotation dynamics model is formulated, and backstepping scheme is used to design an ITRC law such that the states of the closed‐loop system can converge near zero. Then, by taking into consideration the input dynamics, the integrated translational and rotational model is transformed into the form of interconnected system, and thus, the small‐gain theorem can be utilized to guarantee the stability of the over all system. Stability analysis as well as simulation results shows the effectiveness of the presented approach.